L' histoire inhumaine : massacres et génocides des origines à nos jours - Richard, Guy; Cleyet-Merle, Jean-Jacques; Dramani-Issifou, Zakari; Fichou, Jean-Pierre; Fouques, Bernard; Labesse, Jean; Laurens, Henri; Margolin, Jean-Louis (Paris : Armand Colin, 1992)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: genocide